Evaluation of electronic medical record user satisfaction in baros public health center using the end user computing satisfaction model - Putra, Dwi Anantama; Widiyanto, Wahyu Wijaya (Science Midwifery, 2025)
The implementation of Electronic Medical Records (EMRs) has transformed healthcare services by improving accessibility, efficiency, and patient data management. However, user satisfaction remains a significant challenge, affecting the successful adoption and utilization of EMR systems. This study evaluated EMR user satisfaction at UPTD Puskesmas Baros, Kota Sukabumi using the End User Computing Satisfaction (EUCS) model, which assesses five key factors: content, accuracy, format, ease of use, and timeliness. A cross-sectional survey was conducted among 120 healthcare professionals, and the collected data were analyzed using descriptive statistics and multiple linear regression. The results indicated that format had a significant negative impact on satisfaction, suggesting usability issues related to system interface design. While content and accuracy were positively correlated with satisfaction, their effects were not statistically significant. Ease of use and timeliness showed weak correlations, indicating that system efficiency remains a concern. The findings highlight the need for user-centered design improvements and workflow integration strategies to enhance EMR usability. Future research should explore additional factors influencing satisfaction and investigate the long-term effects of system modifications.